TOWARDS ECO-URBAN SETTLEMENT: LEARNING FROM LOW-MID HOUSING VACANCY PHENOMENA IN THE CITY OF BEKASI - A. Adib Abadi (Journal of Architecture&ENVIRONMENT, 2011)
Eco-urban settlement is integrated concept of environment sustainability and urban settlement. As a dominant element in urban area, housing plays a critical role in producing sustainable settlement as it significantly influences physical environmental quality as well as social and economic productivity. The provision of decent housing therefore become strategic approach to produce such a strong urban community that will functions as an importance factor in enhancing urban sustainability. However, it is not a simple idea as housing decency is a conditional aspect with regard to heterogeneous needs and housing characteristics. In dealing with urban housing insufficiency, the Government of Indonesia has introduced a housing ownership program for low to mid income people. This strategy in some extent offers social, economic and environmental benefits and forms strong neighbourhood and communities that will be valuable capital for enhancing urban sustainability. However, this strategy does not present its incentives as it puts its orientation on quantitative measure rather than social aspect. This paper exposes the condition of low-mid income housing policy implementation in relation to eco-urban settlement process. The fact that about 40.2% of abandoned low-mid income houses in the municipality of Bekasi, in West Java, Indonesia indicates the importance of social dimension in dealing with sustainable urban settlement objectives. Regression analysis of data both at macro and micro levels discloses the correlation between low mid people needs and the abandonment. The result shows the importance of integrating social dimension into the housing provision strategy for effectively achievingeco-urban settlement goal.